A Potent Medicine Of Ayurveda: Goghrita - Verma, Vinay Kumar; Nathani, Sumit; Kotecha, Mita (International Research Journal of Ayurveda & Yoga, 2021)
The purpose of this study was to review ancient ayurvedic texts and recent laboratory backed information regarding goghrita. Introduction-Goghrita (Clarified butter made from the milk of a cow) is called as Amritopam which is best among all types of ghrita. It is yogavahi dravya which potentiates the actions of other medicines without changing its own properties. Material and methods- Review of literature was done with the help of ancient Ayurveda books and modern scientific publications and critically analyzed. Results and discussion- Goghrita is having Madhura Rasa; Guru, Snigdha, Mridu Guna; Madhura Vipaka and Sheeta Veerya. It is having Chakshusya, Balya, Vṛisya, Jeevaneeya, Medhya, Vishaghna and Vatapittashamaka properties which is indicated in Jeerṇa jvara, Kshaya, Visha, Daha, Shotha, Shoola, Unmada, Apasmara and many other diseases. Chemically, cow ghee is a complex lipid including glycerides and free fatty acids. The physicochemical parameters like specific gravity, moisture content, saponification value etc. help in assessment of quality of goghrita, thus help in finding adulteration with others types of fat substances. The chemical composition of goghrita revealed presence of triglycerides, free fatty acids, fat soluble vitamins in different proportions, which is crucial for standardization of samples collected from various sources. Goghrita facilitates the absorption and assimilation of food and drug substances in the body thus, acting as a potent vehicle or carrier for drug delivery.